The prisoner Emanuel D’Aranda in Algeria (1640-1642), a loyal servant of Christianity and a staunch lawyer for it - belamri, Fateh (The Algerian Historical Journal, 2026)
The pages of this article shed light on Emanuel d'Aranda, who loyally served Christianity. He is from the Belgian region of Bruges. He lived as a prisoner in the city of Algiers between the years 1640 and 1642, after he was released in a prisoner exchange. Written by: Les Captifs Algeria d'après la relationship of Emanuel d'Aranda Jadis Esclave in Alger (XVIIème Siècle), in which he told us about many stories of prisoners he met in Hammam Ali Betchin in particular, and in the city of Algiers in general, but the reader of this writing will find its author embodying the service Loyal to the Christian religion and defending it boldly. Who is Emmanuel Darenda? What are the contents of his composition? What were his faithful services to Christianity? Was he honest or the opposite? This is what we would like to know.